Keeping the castle : a tale of romance, riches, and real estate - Kindl, Patrice (Viking, 2012)
In order to support her family and maintain their ancient castle in Lesser Hoo, seventeen-year-old Althea bears the burden of finding a wealthy suitor who can remedy their financial problems.